Hubungan antara intensitas penggunaan gadget dengan pola tidur pada remaja - Zakarisma, Afiffah Arundina; Muhlisin, Abi (Holistik Jurnal Kesehatan, 2025)
Background: The use of gadgets has now become a daily necessity for everyone, especially teenagers. In this modern era, the use of gadgets can help all activities in life. The lack of ability and control of each individual in minimizing the use of gadgets can have a negative impact on each individual's sleep patterns. Purpose: To determine the relationship between the intensity of gadget use and sleep patterns in teenagers. Method: Quantitative research type descriptive correlative using cross sectional design. This research was conducted in August-September 2024, at the first Vocational High School of Juwiring Klaten, Mrisen village, Juwiring district, Klaten. The sampling technique used was the probability sampling method with proportional stratified random sampling technique, namely 90 respondents. The inclusion criteria for the selected samples were grade XI students, willing to participate in the research, and having gadgets. The independent variable in this study is the intensity of gadget use, while the dependent variable is sleep patterns. Results: Respondents with moderate and high intensity of gadget use caused poor sleep patterns, namely 46 respondents (54.8%) moderate intensity and 38 respondents (45.2%) high intensity with a p-value of 0.030. Conclusion: There is a relationship between the intensity of gadget use and sleep patterns in teenagers. The higher the intensity of gadget use, the worse the teenager's sleep patterns. Suggestion: It is hoped that schools and parents can be firm in controlling and regulating their teenagers. In order to minimize excessive use of gadgets, so as not to trigger poor sleep patterns.   Keywords: Gadget; Intensity; Sleep Pattern; Teenagers.   Pendahuluan: Penggunaan gadget kini telah menjadi kebutuhan sehari-hari bagi setiap kalangan, khususnya kalangan remaja. Pada era modern ini, penggunaan gadget dapat membantu segala aktivitas pada kehidupan. Kurangnya kemampuan dan kontrol setiap individu dalam meminimalisir penggunaan gadget dapat mengakibatkan dampak buruk pada pola tidur setiap individu. Tujuan: Untuk mengetahui hubungan antara intensitas penggunaan gadget dengan pola tidur pada remaja Metode: Penelitian kuantitatif jenis deskriptif korelatif menggunakan desain cross sectional. Penelitian ini dilaksanakan pada bulan Agustus-September 2024, di SMK 1 Juwiring Klaten, Dusun Mrisen, Kecamatan Juwiring, Klaten. Teknik pengambilan sampel yang digunakan adalah probability sampling dengan teknik proportional stratified random sampling, didapatkan sampel sebanyak 90 responden. Kriteria inklusi sampel yang dipilih yaitu siswa-siswi kelas XI, bersedia mengikuti penelitian, dan memiliki gadget. Variabel bebas dalam penelitian ini adalah intensitas penggunaan gadget, sedangkan variabel terikat adalah pola tidur. Hasil: Responden dengan intensitas penggunaan gadget sedang dan tinggi menyebabkan pola tidur yang buruk, yakni sebanyak 46 responden (54.8%) intensitas sedang dan 38 responden (45.2%) intensitas tinggi dengan perolehan p-value 0.030. Simpulan: Terdapat hubungan antara intensitas penggunaan gadget dengan pola tidur pada remaja. Semakin tinggi intensitas penggunaan gadget, maka semakin buruk pola tidur remaja. Saran: Diharapkan kepada sekolah dan orang tua untuk bisa tegas dalam mengontrol dan mengatur anak remaja mereka. Agar dapat meminimalisir penggunaan gadget yang berlebihan, sehingga tidak memicu pola tidur yang buruk.   Kata Kunci: Gadget; Intensitas; Pola Tidur; Remaja.